Empowering Young Voices - Terri Suico (Study and Scrutiny, 2025)
This review explores Ashley S. Boyd and Janine J. Darragh’s Reading for Action: Engaging Youth in Social Justice through Young Adult Literature and Reading for Justice: Engaging Middle Level Readers in Social Action through Young Adult Literature. These books offer educators a plethora of resources and ideas for using young adult literature to help readers find their voices and raise awareness on issues related to equity and justice.